Embracing support: Women’s preferences and challenges for husband’s companionship during labor in the Indian context - A cross-sectional study - Rakhi Gaur; Priyanka Rai; Bhavna Verma; Neha Suyal; Rashmi Bala Patel (Journal of Family Medicine and Primary Care)
Aims and Objectives: India has observed a substantial reduction in its maternal mortality ratio, dropping from 130 in 2014-16 to 97 per lakh live births in 2018-20, there is a pressing need to further enhance maternal safety and minimize mortality rates. To expedite these efforts, involving husbands as labor companions during childbirth is crucial. This research aimed to assess women’s desirability and the perceived barriers regarding the presence of their husbands as companions during labor in India. Methods: Focusing on a cross-sectional design, we opted for a sample of 402 pregnant women using a nonprobability convenient sampling technique. The participants were 18 years and older, in any trimester of pregnancy, and had previously attended antenatal clinics (ANC) at specific hospitals in Jharkhand. Data collection was done through a self-structured questionnaire, and both descriptive and inferential analyses were conducted. Results: Most of the participants (84.07%) desired companionship with husband during labor. Top three perceived barriers reported by participants were, companionship with females only since ancient times (93.0%), hospital policies (92.0%), and inconvenient for other laboring women due to presence of male (90.5%). Educational level, area of residence, and age were significantly associated with almost all components of desirability with husband’s companionship (P < 0.05). Conclusion: In Western countries, the idea of having partners present during labor and delivery is widely accepted. However, in Indian settings, stakeholders must work on formulating a proficient childbirth policy that promotes the participation of male partners, incorporating them into the process as well.